Author Correction: EpCAM-dependent extracellular vesicles from intestinal epithelial cells maintain intestinal tract immune balance - Lingling Jiang (Nature Portfolio, 2020)
An amendment to this paper has been published and can be accessed via a link at the top of the paper.